Implementation Of Social Studies In Elementary Schools In The National Curriculum In Private Schools (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The purpose of this study is to investigate how Social Studies is taught in private primary schools using the National Curriculum framework, namely the Independent Curriculum. The study focuses on teaching methods, character education integration, and the various enabling and impeding elements that influence curriculum implementation. To gain a thorough understanding of instructors' experiences presenting the curriculum, a qualitative research approach with a basic qualitative design was employed. Three teachers from grades 4, 5, and 6 at MIS Hayatul Islamiyah, Depok, were selected using purposive sampling, and the population consists of social studies instructors at private primary schools. Semi-structured interviews accompanied by field notes and documentation were used to gather data. An open-ended interview guide encompassing topics such as lesson planning, teaching techniques, evaluation tactics, and the integration of character education served as the primary tool. As teachers navigate opportunities and challenges in connecting their curriculum with national education goals, the data reveal a range of dynamics in the implementation process. In addition to offering suggestions for improving the standard of Social Studies education moving forward, this study provides a comprehensive overview of current practices in private school settings.